2005
DOI: 10.1590/s1519-566x2005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Diapause in fruit fly parasitoids in the Recôncavo Baiano, Brazil

Abstract: Neotropical Entomology 34(4): 613-618 (2005) Diapausa em Parasitóides de Moscas-das-Frutas no Recôncavo Baiano RESUMO -A diapausa tem sido pouco estudada em moscas-das-frutas e seus parasitóides em regiões de clima tropical. Este trabalho é o primeiro registro da diapausa em parasitóides de larva-pupa de tefritídeos no Recôncavo Baiano. A diapausa foi observada em quatro espécies nativas [Doryctobracon areolatus (Szépligeti)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…For P. humilis and P. lounsburyi, overwintering development was linked to temperature in each year of the study, suggesting these parasitoids do not have a winter diapause; species that do not diapause are often less cold-tolerant (Hance et al 2007). While some fruit ßy parasitoid species from temperate and tropical regions in Asia and the Americas are known to enter diapause (Aluja et al 1998, Carvalho 2005, none from subtropical Africa have been reported. Without a diapause it is critical for adult P. humilis and P. lounsburyi to Þnd hosts soon after they emerge in early spring.…”
Section: Discussionmentioning
confidence: 99%
“…For P. humilis and P. lounsburyi, overwintering development was linked to temperature in each year of the study, suggesting these parasitoids do not have a winter diapause; species that do not diapause are often less cold-tolerant (Hance et al 2007). While some fruit ßy parasitoid species from temperate and tropical regions in Asia and the Americas are known to enter diapause (Aluja et al 1998, Carvalho 2005, none from subtropical Africa have been reported. Without a diapause it is critical for adult P. humilis and P. lounsburyi to Þnd hosts soon after they emerge in early spring.…”
Section: Discussionmentioning
confidence: 99%
“…Results are in concordance with those obtained previously with other hosts species (Ashley et al 1976;Carvalho, 2005;Appiah et al 2013). Only the offspring sex-ratio parameter remained untestable due to lack of data in some months.…”
Section: Biotic and Abiotic Factors Affecting Parasitic Activity Of Dsupporting
confidence: 90%
“…The majority of diapausing individuals (86%, involving the five parasitoid species found in this study) extended diapause for a given predictable unsuitable season, like winter, whereas a minor proportion (including only D. brasiliensis, D. areolatus and A. pelleranoi) extended diapause between 12 and 14 months. A very long diapause period in D. areolatus (414 days) was previously reported by Carvahlo (2005) working in a tropical forest from north-eastern Brazil, whereas Aluja et al (1998) in Central Mexico reported that diapause in both D. areolatus and A. pelleranoi is common and that it can last up to 11 months. Prolonged diapause enables the emergence of a given genotype of the insect population to provide a better emergency distribution in time, thereby allowing certain progenies to reproduce in more suitable conditions (Hanski 1988;Hopper 1999;Menu et al 2000), whether it is at the competitive level regarding its peers, increased availability of hosts or by abrupt environmental changes.…”
Section: Discussionmentioning
confidence: 67%
“…Diapause in fruit fly parasitoids has been mainly reported in temperate regions (Prokopy 1968;Maier 1981;AliNiazee 1985;Hoffmeister 1992;Gut & Brunner 1994), but this phenomenon has also been recorded in tropical environments (Pemberton & Willard 1918;Darby & Knapp 1934;Aluja et al 1998;Carvahlo 2005). Aluja et al (1998) and Carvahlo (2005) working in tropical forests from Mexico and Brazil, respectively, found ecological evidence for diapause in D. areolatus, U. anastrephae and A. pelleranoi, three of the five most abundant parasitoid species spread throughout Yungas forest in north-western Argentina.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation